What You Don’t Know Can Hurt You: Uncertainty Impairs Executive Function - Alquist, Jessica L.; Baumeister, Roy F.; Tice, Dianne M.; Core, Tammy J. (Frontiers in Psychology, 2020)
Three studies demonstrated that situational uncertainty impairs executive function on subsequent unrelated tasks. Participants were randomly assigned to either uncertain situations (not knowing whether they would have to give a speech later, Studies 1-2; uncertain about how to complete a task, Study 3) or control conditions. Uncertainty caused poor performance on tasks requiring executive function that were unrelated to the uncertainty manipulation. Uncertainty impaired performance even more than certainty of negative outcomes (might vs. definitely will have to make a speech). A meta-analysis of the experimental studies in this package found that the effect is small and reliable. One potential explanation for this effect of uncertainty on executive function is that uncertainty is a cue for conserving effort.